2003
DOI: 10.1080/15287390309353768
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Risk of B-Lymphocyte Malignancies in Industrial Cohorts

Abstract: Among numerous studies of occupational groups with varied chemical exposures (e.g., farmers, petroleum workers, and rubber workers), some have reported excess risk for non-Hodgkin's lymphoma (NHL), multiple myeloma, and other cancers of the B-lymphocyte cell line. While not conclusive, these studies raise questions about the effects of chemical exposures on the lymphocytic versus myeloid cell lines. Almost 70 occupational cohort studies were identified that addressed B-cell cancer risks in 9 major industrial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…CLL is considered a subtype of non-Hodgkin lymphoma (NHL), as both are lymphoid cell malignancies ( Jaffe et al , 2001 ). A review of 68 industrial studies reported several elevated findings for lymphoid cancers (CLL, NHL, multiple myeloma) for rubber workers and cohorts exposed to multiple chemicals ( Bukowski et al , 2003 ). Possibly a more complex environment such as a refinery compared with terminals might tend to show an increased risk for lymphoid tumours such as CLL.…”
Section: Discussionmentioning
confidence: 99%
“…CLL is considered a subtype of non-Hodgkin lymphoma (NHL), as both are lymphoid cell malignancies ( Jaffe et al , 2001 ). A review of 68 industrial studies reported several elevated findings for lymphoid cancers (CLL, NHL, multiple myeloma) for rubber workers and cohorts exposed to multiple chemicals ( Bukowski et al , 2003 ). Possibly a more complex environment such as a refinery compared with terminals might tend to show an increased risk for lymphoid tumours such as CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality from some diseases associated with smoking and alcohol (cirrhosis of liver and respiratory diseases) was not elevated, although heart disease mortality, particularly ischemic heart disease in men, did not show a "healthy worker" effect [ 27 ]. Myeloma risk has not been associated with smoking and alcohol use [ 28 , 29 ], but it has been linked to occupational chemical exposures [ 30 , 31 ]. It is also unlikely that regional differences contributed to the observed excesses in mortality from intestinal and liver cancers or myeloma since state- and county-based SMRs (not shown) were similar to those using U.S. referent rates.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the human reports have decided that 1,3-butadiene and dioxins are significant human carcinogens, 13 14 while others give more cautious ''probable'' or ''possible'' verdicts [15][16][17] and yet others report doubtful or negative effects. [18][19][20][21] Two mass exposure episodes to carcinogens so far remain uninformative including the major escape of dioxins at Seveso and a possible relation between an alleged leukaemia epidemic in Basra and the Gulf war oil well fires in Kuwait and southern Iraq. These uncertainties have inhibited any consistent public health policy.…”
Section: Policy Implicationsmentioning
confidence: 99%